Narrative battles: competing discourses and diplomacies of Sudan's "southern problem", 1961-1991 - Manoeli, S (2017)
This dissertation explores the discursive and diplomatic feud between Southern Sudanese rebels in exile and the Sudanese government from 1961 to 1991. It argues that the discursive battle waged for international legitimacy represents a strategic, but often overlooked aspect of the wars in Southern Sudan. The "Southern Problem" – a popular phrase for the series of debates surrounding the political status of Southern Sudan, as a region of a unitary Sudan, an autonomous part of a federal Sudan or an independent state – constituted the focus of the feud. The thesis traces the competing constructions of the "Problem" by a series of rebel groups from Southern Sudan and Sudanese governments, specifically designed for international audiences, and how they interacted abroad. During the thirty-year window, 1961-1991, in which the global Cold War served as the backdrop, the thesis shows that each of the discursive competitors drew on lexicons and logics that were internationally resonant during those historical moments, which rendered the "Southern Problem" legible to various audiences. It charts the shifting discourses constructed amidst the intellectual ferments of Pan-Africanism, Black liberation politics, decolonisation, and socialist internationalism. The thesis traces the construction, dissemination, reception and reproduction of these discourses, through a variety of uneven networks. It shows how they were refracted through the local politics of audiences, and were reframed over time for a variety of political purposes. These discourses were consequential abroad: they informed diplomatic action and efficacy; rebel discourses in particular shaped the political subjectivities of ordinary Southern Sudanese refugees and rebels in exile. By using the large corpus of rebel writings and of Sudan's diplomatic texts, as well as oral history and memoirs, the thesis addresses questions neglected in the literatures regarding the intellectual and socio-historical aspects of the transnational relations of Southern Sudanese rebels.